Nikah Sirri and its Responses from Religious Court: Taking Sides between Acceptation and Refutation - Titis Thoriquttyas (Justicia Islamica, 2017)
This paper describes on the regulation of nikah sirri and its responds from the various society, especially from the religious leader’s view in Madura. Criminalizing the subject of nikah sirri become debatable issues for Madurese community in the socially and religiously context. Either the acceptations or refutations for this case become the crucial point to discuss academically because both of responses supported by the logical argumentations. It considered as the progressive policy to minimize it cases and protect the rights of wife and children legally, socially and economically. In other side, the criminalizing regulation viewed as the overlapping law because it reduction the Islamic Law. In order to bridge this case, the leader communities played the significant role to mediate it through the legal frameworks.   Furthermore, this paper aims to provide the position of criminalizing regulation for the subject of nikah sirri as well as the role of leader communities in Madura to mediate the differs argumentations behind it. In conclusion, the researcher believed that the leader communities in Madura have the opportunities to solve the problems of nikah sirri based on the religious, social and cultural reasons.